2006
DOI: 10.1381/096089206775221998
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Psoriasis after Open Gastric Bypass

Abstract: Psoriasis is a frequent skin disease, affecting 2% of the world's population. Stress, alcohol, smoking and obesity may be associated with psoriasis. A 56-year-old man with BMI 46.9 kg/m(2), hypertension and gastroesophageal reflux, had severe psoriasis for the last 39 years, without any remission on multiple treatments. Psoriatic papules and plaques were noted on his face, dorsum of hands, buttocks, knees, and elbows. He underwent open Roux-en-Y gastric bypass. At 4-month follow-up, the patient had lost 23 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 22 publications
1
54
0
2
Order By: Relevance
“…In obese patients, there is a significant positive correlation between serum levels of TNF-α and waist-hip ratio, serum levels of soluble TNF-α receptor 1 and body weight, and soluble TNF-α receptor 2 and BMI [29,30,31]. It has been documented that fasting may improve, at least temporarily, inflammatory conditions including psoriasis [32, 33] and there are case reports of psoriasis remission after surgery for obesity [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In obese patients, there is a significant positive correlation between serum levels of TNF-α and waist-hip ratio, serum levels of soluble TNF-α receptor 1 and body weight, and soluble TNF-α receptor 2 and BMI [29,30,31]. It has been documented that fasting may improve, at least temporarily, inflammatory conditions including psoriasis [32, 33] and there are case reports of psoriasis remission after surgery for obesity [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between weight loss and psoriasis severity remains to be elucidated, but several case studies have shown that weight loss from gastric bypass surgery results in remission of psoriasis. 45,46 Depression Depression is associated with increased risk of cardiovascular disease. 47,48 Psoriasis is associated with lack of self-esteem and increased prevalence of mood disorders including depression.…”
Section: Obesitymentioning
confidence: 99%
“…There are case reports of complete remission of severe psoriasis with the discontinuation of all psoriasis medications after substantial weight loss as a result of gastric bypass surgery [14,15,16]. More recently, it has been shown that obese patients with moderate-to-severe psoriasis increase their response to low-dose cyclosporine if calorie-controlled diet is included in the treatment regimen [17].…”
Section: Introductionmentioning
confidence: 99%